Processing and properties of silica-bonded porous nano-SiC ceramics with extremely low thermal conductivity. Issue 7 (July 2020) - Kim, Yong-Hyeon; Kim, Young-Wook; Seo, Won-Seon
Abstract: Silica-bonded porous nano-SiC ceramics with extremely low thermal conductivity were prepared by sintering nano-SiC powder-carbon black template compacts at 600–1200 °C for 2 h in air. The microstructure of the silica-bonded porous nano-SiC ceramics consisted of SiC core/silica shell particles, a silica bonding phase, and hierarchical (meso/macro) pores. The porosity and thermal conductivity of the silica-bonded porous nano-SiC ceramics can be controlled in the ranges of 8.5–70.2 % and 0.057–2.575 Wm −1 K −1, respectively, by adjusting both, the sintering temperature and template content. Silica-bonded porous nano-SiC ceramics with extremely low thermal conductivity (0.057 Wm −1 K −1 ) were developed at a very low processing temperature (600 °C). The typical porosity, average pore size, compressive strength, and specific compressive strength of the porous nano-SiC ceramics were ∼70 %, 50 nm, 2.5 MPa, and 2.7 MPa·cm 3 /g, respectively. The silica-bonded porous nano-SiC ceramics were thermally stable up to 1000 °C in both air and argon atmospheres.